Racial Discrimination in Local Public Services: A Field Experiment in the US - Corrado Giulietti; Mirco Tonin; Michael Vlassopoulos (Institute for the Study of Labor (IZA), 2015)
Discrimination in access to public services can act as a major obstacle towards addressing racial inequality. We examine whether racial discrimination exists in access to a wide spectrum of public services in the US. We carry out an email correspondence study in which we pose simple queries to more than 19,000 local public service providers. We find that emails are less likely to receive a response if signed by a black-sounding name compared to a white-sounding name. Given a response rate of 72% for white senders, emails from putatively black senders are almost 4 percentage points less likely to receive an answer. We also find that responses to queries coming from black names are less likely to have a cordial tone. Further tests demonstrate that the differential in the likelihood of answering is due to animus towards blacks rather than inferring socioeconomic status from race.
Keywords: D73; H41; J15; 330; discrimination; public services provision; school districts; libraries; sheriffs; field experiment; correspondence study